Epidemiological and Clinical Presentation of Retinoblastoma among Nepalese Children in 2019 - Limbu, Ben; Kafle, Prerna Arjyal; Lamichanne, Diwa Hamal; Pant, Suresh Raj; Shakya, Samyek; Rasaily, Suresh B.K. (South Asian Journal of Cancer, 2022)
Objectives Retinoblastoma (RB) is rare but potentially fatal if left untreated. This study aimed to evaluate the epidemiological profile, clinical manifestation, classification, and affordability of RB treatment among Nepalese children in the year 2019.Materials and Method A multicentric, multiethnic hospital-based cross-sectional study after ethical approval from the National Health Research Council was conducted from January 2019 to December 2019 by incorporating ophthalmologists all over the nation. Twenty-seven RB centers were selected. All the RB presented in the RB centers either newly diagnosed or ongoing treatment consented to the study were included and failed to consent for the study, RB survivors were excluded from the study. Data based on demographic profile, clinical manifestation, ethnical and geographical distribution, and treatment received were collected in the customized Google Form. Each case was classified at the time of diagnosis as per the International Classification of Retinoblastoma groups and different treatment modalities offered as per grouping and staging. The affordability of treatment was calculated using a catastrophic approach.Statistical Analysis Data were entered into Microsoft Excel 2010 and analyzed using Statistical Package for Social Sciences version 20.Result A total of 34 RB cases, 21 (61.76%) in ongoing treatment group and 13 (38.2%) in newly diagnosed group presented in the RB centers. Out of total, 32 (64.7%) had unilateral and 12 (35.3%) cases had bilateral involvement. The majority of patients was from Province 1 (35.3%) and belonged to the upper caste (38.2%). Leukocoria was the most common presentation (73.9%) followed by proptosis, red eye, and phthisis bulbi. More than 75% patients presented at advanced group D (54%) and E (21%) and stage 0 (90%). More than 90% of patients received systemic chemotherapy, and 42.6% received transpupillary thermotherapy. The average cost of RB treatment was estimated to be 521% of the nonfood expense of the family which is unaffordable to almost all cases (100%).Conclusion Leukocoria is the most common mode of clinical presentation in both unilateral and bilateral RBs. Early diagnosis and appropriate treatment are key to success for saving life, sight, and eye. However, community awareness programs against RB, active referral networks, and the establishment of chemotherapy centers with trained human resources are needed to reduce loss of life, sight, and eye.
Keywords: affordability; chemotherapy; clinical presentation; epidemiology; ethnicity; retinoblastoma